Socioeconomic Inequality in Childhood Obesity - Moradi, Ghobad (J Res Health Sci, 2017)
Background: The aim of this study was to assess the socioeconomic inequalities in obesity and overweight in children aged 10 to 12 yr old. Study design: A cross-sectional study. Methods: This study was conducted on 2506 children aged 10 to 12 yr old in the city of Sanandaj, western Iran in 2015. Body mass index (BMI) was calculated. Considering household situation and assets, socioeconomic status (SES) of the subjects was determined using Principal Component Analysis (PCA). Concentration Index was used to measure inequality and Oaxaca decomposition was used to determine the share of different determinants of inequality. Results: The prevalence of overweight was 24.1% (95% CI: 22.4, 25.7). 11.5% (95% CI: 10.0, 12.0) were obese. The concentration index for overweight and obesity, respectively, was 0.10 (95% CI: 0.05, 0.15), and 0.07 (95% CI: 0.00, 0.14) which indicated inequality and a higher prevalence of obesity and overweight in higher SES. The results of Oaxaca decomposition suggested that socioeconomic factors accounted for 75.8% of existing inequalities. Residential area and mother education were the most important causes of inequality. Conclusions: To reduce inequalities in childhood obesity, mother education must be promoted and special attention must be paid to residential areas and children gender.